Pengembangan UMKM Kuliner dengan Digitalisasi Marketing - Ella Anastasya Sinambela; Didit Darmawan (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
MSMEs are one of the economic sectors that have a significant impact on the country's economy. Especially in the digital era with the use of the internet which is quite massive among the community. However, this is not done by several culinary MSME players in Kepuhkiriman Village, Sidoarjo. This PKM activity is aimed at providing assistance to 15 culinary MSME players. The method used in this activity is the Participatory Action Research (PAR) method. The implementation of PKM is carried out in four stages, namely, preparation, implementation, evaluation, and reporting. The results of the activity show that MSME players have successfully used digital marketing media and obtained orders through the content produced.